Rethinking the conceptual terrain of AIDS scholarship: lessons from comparing 27 years of AIDS and climate change research - Brklacich Michael; Chazan May; Whiteside Alan (BMC, 2009)
Abstract Background While there has recently been significant medical advance in understanding and treating HIV, limitations in understanding the complex social dimensions of HIV/AIDS epidemics continue to restrict a host of prevention and development efforts from community through to international levels. These gaps are rooted as much in limited conceptual development as they are in a lack of empirical research. Methods In this conceptual article, the authors compare and contrast the evolution of climate change and AIDS research. They demonstrate how scholarship and response in these two seemingly disparate areas share certain important similarities, such as the "globalization" of discourses and associated masking of uneven vulnerabilities, the tendency toward techno-fixes, and the polarization of debates within these fields. They also examine key divergences, noting in particular that climate change research has tended to be more forward-looking and longer-term in focus than AIDS scholarship. Conclusion Suggesting that AIDS scholars can learn from these key parallels and divergences, the paper offers four directions for advancing AIDS research: (1) focusing more on the differentiation of risk and responsibility within and among AIDS epidemics; (2) taking (back) on board social justice approaches; (3) moving beyond polarized debates; and (4) shifting focus from reactive to forward-looking and proactive approaches.